Fat Overload Focal Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Two 9-year-old patients receiving fat emulsion therapy (FET) who presented with focal seizures and other neurologic complications are reported from the Baylor College of Medicine, Neurology Service, Texas Children's Hospital, Houston, TX.